The Perspectıve of X and Y Generations on Deterrence of Death Penalty: The Case of Women Murders in Turkey - Yeliz Yazan; Betü l Solmaz (Journal of Management Practices, Humanities and Social Sciences, 2018)
This study aims to address death penalty in context of crime and punishment and evaluate the impact of restate of death penalty on women murders in Turkey by examining opinion of generations. The study aims to analyze not only the deterrent effect of death penalty but also different view- points of generations regarding this topic. To achieve this aim, a survey is conducted such that a questionnaire was made through social media for 460 people composed of X and Y generations who had various education levels. Chi-Square analysis is used in the obtained data. The results highlight that the views of not only X and Y generation but also rest of them support the idea of restating death penalty. According to them, referendum should be made for death penalty. On the basis of the responses from the respondents and analysis results, recommendations are made and implications of the study for policy makers are discussed.